Visual Field Changes in Idiopathic Intracranial Hypertension Treated with Oral Acetazolamide (Journal of Enam Medical College, 2025)
Background: Idiopathic Intracranial Hypertension (IIH) is a disorder primarily among overweight women of childbearing age. Acetazolamide (AZM) is commonly used to treat IIH, but there is insufficient information regarding VF changes in response to treatment with this drug. Objective: This study was designed to evaluate the visual field changes of patients with IIH treated with oral acetazolamide. Materials and Methods: A total of 30 patients with IIH treated with oral acetazolamide (500 mg twice daily) were followed up after 3 months and 6 months. Demographic features were recorded. Visual field analysis was done and papilledema was graded accordingly. Mean value of perimetric mean deviation of the follow-up periods were compared with that of baseline values. Results: The mean age of the study patients was 25.3±8.7 years with a female predominance (83.3%).  Most common field defect was nasal or temporal field defects (46.67% in their right eye and 50.0% in their left eye). The mean of perimetric mean deviation (PMD) and papilledema of both eyes were reduced significantly over time. This study concluded that oral acetazolamide 500 mg twice daily is effective in reduction of symptoms/signs and improve perimetric mean deviation in visual filed among patients with idiopathic intracranial hypertension with minimum side effects. Conclusion: Changes in visual field parameter are important marker in diagnosis and monitoring of patients of IIH treated with oral acetazolamide.J Enam Med Col 2022; 12(3): 122−126